Literature on technological capability: past, present and future. Issue 4 (23rd December 2020) - Tello-Gamarra, Jorge; Fitz-Oliveira, Mônica
Abstract : Purpose: The purpose of this paper is to identify the main theoretical bases from the past and the present, as well as to determine the future perspectives for technological capability research. Design/methodology/approach: To achieve this, the study used the bibliometric method, which is based on two research strategies, co-citation analysis and bibliographical coupling analysis with database Scopus and software VOS viewer. Findings: The main result was the identification of the theoretical bases from the past: absorptive capacity, innovation and core competence; as well as the current bases: innovation capability, firm performance and knowledge transfer. The future perspectives of technological capability are guided by keyword coupling, generating three theoretical perspectives: business development, sustainability and future technologies. Originality/value: There are no studies in the literature that analyze the theoretical bases of technological capability, identifying common aspects and different approaches. Thus, this study is of original nature and the research method, composed of bibliometric analyzes and the coupling of emerging keywords, which are a part of the future perspectives, which permitted the authors to achieve the proposed goal.